The competitive consumption and fetishism of wildlife trophies. (May 2019) - Simon, Alexander
This article argues that trophy hunting is not an ahistorical phenomenon. Hunting for sport became popular among US elites in the late 1800s. Since this time, in addition to animal trophies being displayed as evidence of one's economic and cultural capital, these commodities have served as symbolic evidence of their owner's courage, skill, and fortitude. Currently, the hunting industry (i.e. sporting goods retailers, weapons manufacturers, and advertising supported media) seeks to perpetuate and expand these perceptions. Displaying animal trophies is unlike many other forms of competitive consumption, such as displaying expensive jewelry, in that the hunting industry has attempted to create the often false perception that these commodities required their owners to conquer dangerous and cunning opponents. Trophy hunting is unlike many other sports, in that economic resources, as opposed to skill, are often the primary factor in determining one's success. Therefore, the use values of animal trophies are fetishized.